2019
DOI: 10.3390/ani9110971
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnostics of Freemartinism in Polish Holstein-Friesian Female Calves

Abstract: Simple SummaryFreemartinism is the most common type of gender developmental disorder, resulting in infertility of heifers from multiple-sex twin pregnancies. The frequency of this syndrome is related to the frequency of multiple pregnancies, the number of which has significantly increased in dairy cattle populations (HF). Therefore, rapid diagnostics is necessary to enable early elimination of heifers with freemartinism from breeding. The aim of the study was to compare and identify the best method for early i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…10 In cattle, freemartinism affects > 90% of heifers born from a heterosexual twin pregnancy 3 whereas in sheep, the incidence is as low as 1-5% in male-bearing multiple pregnancies. 6,10 The more common development of vascular placental anastomosis between fetuses is responsible for the high incidence of freemartin in cattle 11 but this phenomenon is less frequent in small ruminants. 2,3 It has been suggested that in highly prolific sheep breeds, male-bearing pregnancies with 4 or 5 lambs might present an increased risk for freemartinism, potentially due to increased placental contact between fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…10 In cattle, freemartinism affects > 90% of heifers born from a heterosexual twin pregnancy 3 whereas in sheep, the incidence is as low as 1-5% in male-bearing multiple pregnancies. 6,10 The more common development of vascular placental anastomosis between fetuses is responsible for the high incidence of freemartin in cattle 11 but this phenomenon is less frequent in small ruminants. 2,3 It has been suggested that in highly prolific sheep breeds, male-bearing pregnancies with 4 or 5 lambs might present an increased risk for freemartinism, potentially due to increased placental contact between fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers report that the in vitro method of acquiring calves entails complications, including heavier embryos resulting in more difficult deliveries (Behboodi et al, 1995;Breukelman et al, 2005;Kruip & den Haas, 1997;Numabe et al, 2000), slower development (Max, 2016), higher oxygen consumption, lipid accumulation, DNA methylation and mixoploidy (Hansen, 2020a(Hansen, , 2020bViuff et al, 1999), as well as chromosomal anomalies (Block et al, 2003;Bonilla et al, 2013;Iannuzzi et al, 2021;Kozubska-Sobocińska et al, 2019;van Wagtendonk-de Leeuw et al, 1998). Viuff et al (1999), Dieleman et al (2002), Tšuiko et al (2017), Catteeuw (2018) and Hansen (2020aHansen ( , 2020b found that chromosomal anomalies were more common in in vitro embryos than in those obtained in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The affected females are sterile due to their underdeveloped reproductive systems. In dairy cattle breeds, an increased trend of twin pregnancies is observed, and this type of DSD is thus considered a serious health and breeding problem [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%